2015
DOI: 10.17159/sajs.2015/20140164
|View full text |Cite
|
Sign up to set email alerts
|

A review of quantitative studies of South African youth resilience: Some gaps

Abstract: Resilience (positive adjustment to hardship) relies on a socioecologically facilitated process in which individuals navigate towards, and negotiate for, health-promoting resources, and their social ecology, in return, provides support in culturally aligned ways (Ungar, Trauma Violence & Abuse 2013;14(3):255–266). In the light of international critiques of the conceptualisation and measurement of resilience, the aim of this study was to systematically review quantitative studies of South African youth resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
(240 reference statements)
0
18
0
Order By: Relevance
“…However, few such studies in African countries exist outside of South Africa, and there are even fewer quantitative studies of factors contributing to resilience in African youth. Recent review of studies of resilience in youth in South Africa found that positive cognitive appraisal, and internal locus of control, a sense of self-worth, and a preference for socially appropriate behavior were important individual-level protective factors, but the reviews noted that the majority lacked a culturally or contextually sound measurement [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…However, few such studies in African countries exist outside of South Africa, and there are even fewer quantitative studies of factors contributing to resilience in African youth. Recent review of studies of resilience in youth in South Africa found that positive cognitive appraisal, and internal locus of control, a sense of self-worth, and a preference for socially appropriate behavior were important individual-level protective factors, but the reviews noted that the majority lacked a culturally or contextually sound measurement [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…These may not manifest until adulthood. Vulnerability factors include challenging social ecosystem such as violent living condition, adverse life events such as death of parents and biological factors such as genetic predispositions (Van Rensburg et al, 2015) The poor health outcomes are varied and include alcoholism, chronic obstructive pulmonary disease, depressive disorders, malignancies, obesity, increased suicidal behaviour, ischemic heart disease and multiple other illnesses (Franke, 2014).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…It is the experience that has emerged from adversities with good outcomes (Daniel, 2010). Initially, it was thought as a person-centred matter; however, later it was revealed as complex interactions between an individual and his/ her surrounding ecology (Van Rensburg et al, 2015). Resilience is the capability of positive adaptations or the ability to maintain or regain mental health, despite experiencing adverse situations (Franke, 2014;Wood & Bhatnagar, 2015;Moreno et al, 2016).…”
Section: Resiliencymentioning
confidence: 99%
“…It should be stressed that most empirical studies based on the concept of resilience are quantitative (e.g. Ostaszewski et al, 2008Ostaszewski et al, , 2009Ostaszewski et al, , 2011Zara, Farrington, 2010;Van Rensburg et al, 2015;Muntean, Cojocaru, 2016). This means that their authors posit a set of factors and disordered behaviours, which are determined as important in the course of statistical analysis.…”
Section: Protective and Risk Factors In The Resilience Conceptmentioning
confidence: 99%